Examining the open building movement through the adaptive reuse of Toma Church in Turkiye - Olgun, Tuba Nur; Akarsu, Ibrahim Kursat (Emerald Group Publishing Ltd, 2026)
PurposeThis study explores the adaptive reuse of Toma Church through the principles of the open building (OB) approach, considering sustainable conservation and functional flexibility goals.Design/methodology/approachA qualitative research approach was adopted, incorporating architectural documentation, literature review, analytical evaluation and spatial comparison.FindingsThe proposed design plan includes modular partitions, portable service units and flexible circulation systems to ensure long-term adaptability without compromising architectural authenticity. Additionally, spatial modifications enhanced accessibility and integration with the urban fabric and transformed the Church into an active public space rather than a static heritage site.Originality/value The findings demonstrate that the OB approach not only preserves the historical and architectural value of heritage buildings but also ensures their sustained relevance within social and urban contexts. This study contributes to the field of sustainable conservation by demonstrating that OB principles provide a practical model for the adaptive reuse of cultural heritage buildings.
Keywords: Open building; Adaptive reuse; Historic church; Conservation